Influence Active Mathematics to Ability Getting to Know the Concept Measurement Child Age 5-6 Year in Tk Three Human Gems New York - Febriani, Qeysha Alea; Solfiah, Yeni; Kurnia, Rita (Journal of English Language and Education, 2025)
Learning draft measurement in park children Still tend passive, so that not enough support children's understanding optimally. This study aims to determine the effect of the Active Mathematics model on the ability to recognize measurement concepts in children aged 5-6 years at Tri Insani Permata Kindergarten. The study used a quantitative approach with a pretest and posttest experimental design. The sample consisted of 15 children who were given treatment through the Active Mathematics model. Data analysis was carried out statistically to measure the effectiveness of the treatment. An increase was obtained significant on the average score of measurement recognition ability, from 13.27% (Starting to Develop category) to 78.96% (Very Well Developing category). The Active Mathematics Model has been proven to have a significant effect on increasing the ability to recognize measurement concepts, with a contribution of 64.06% which is included in the moderate category.